Exploring Relationship Of Architecture, Digital Place Making, And Time: A Systematic Review - Radya Wafi Adyatma; I Gusti Ngurah Antaryama; Arina Hayati (Universitas 17 Agustus 1945, 2026)
This study investigates the relationship between architecture, digital placemaking, and time, addressing theoretical gaps and their relation. While digital placemaking has seen significant advancements, its integration with architecture and temporal dynamics remains insufficiently explored. To bridge this gap, the research conducts a systematic literature review (SLR) of 448 articles published between 2014 and 2024, with 23 selected for in-depth analysis. Using qualitative content analysis, the study identifies key intersections between these domains. Findings reveal that contemporary architecture is fundamentally transformed by digital technology as design strategy to shape how places connect across time that could connect collective memory. By uncovering critical dynamics between architecture, time, and digital placemaking, the study proposes a theoretical framework to guide future research and innovative design strategies. Emphasizing the interplay of spatial and temporal interactions in architectural design, this research enhances understanding and provides a foundation for projects that align with the evolving demands of digital placemaking, ultimately shaping human experiences in digitally augmented environments.